Effect of morphology and support of copper nanoparticles on basic ovarian granulosa cell functions. Issue 5 (27th May 2020) - Sirotkin, Alexander V.; Radosová, Monika; Tarko, Adam; Martín-García, Iris; Alonso, Francisco
Abstract: The aim of this survey is to explore the possible effects of unsupported and supported copper nanoparticles (CuNPs) of different morphologies on basic ovarian cell functions. For this purpose, we have compared the activity of unsupported spherical, triangular, and hexagonal CuNPs, as well as of spherical CuNPs supported on titania, zeolite Y and activated charcoal (0, 1, 10, or 100 ng/mL) on cultured porcine ovarian granulosa cells. Cell viability, proliferation (accumulation of proliferating cell nuclear antigen, PCNA), apoptosis (accumulation of Bcl-2-associated X protein, bax) and release of steroid hormones progesterone, testosterone, and 17 β -estradiol have been analyzed by the Trypan blue test, quantitative immunocytochemistry, and ELISA, respectively. Cell viability decreased after treatment with hexagonal CuNPs, whilst all the other CuNPs increased it. Unsupported spherical and hexagonal CuNPs, and spherical CuNPs/titania reduced PCNA accumulation; in contrast, an increase was noted for unsupported triangular CuNPs and CuNPs/zeolite Y. Bax accumulation was not affected by hexagonal CuNPs, whereas CuNPs/zeolite Y promoted it and all the other CuNPs depleted it. The release of all steroid hormones was inhibited by CuNPs/titanium dioxide and stimulated by CuNPs/charcoal, whilst CuNPs/zeolite Y promoted the testosterone and 17 β -estradiol output, but not that of progesterone. These results demonstrate the direct, mainly stimulatory, impact of CuNPs on basic ovarian cell functions. The character of the CuNPs' action depends on their shape and support. Therefore, CuNPs with appropriate chemical modification could be potentially useful for the control of reproductive processes and treatment of reproductive disorders.